Proceedings of the Twenty-Ninth Annual ACM-SIAM Symposium on Discrete Algorithms 2018
DOI: 10.1137/1.9781611975031.14
|View full text |Cite
|
Sign up to set email alerts
|

Metric Violation Distance: Hardness and Approximation

Abstract: Metric data plays an important role in various settings, for example, in metric-based indexing, clustering, classification, and approximation algorithms in general. Due to measurement error, noise, or an inability to completely gather all the data, a collection of distances may not satisfy the basic metric requirements, most notably the triangle inequality. In this paper we initiate the study of the metric violation distance problem: given a set of pairwise distances, modify the minimum number of distances suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 20 publications
(17 reference statements)
1
41
0
Order By: Relevance
“…Hence, we would need a general metric repair algorithm. Fan, et al [18] present an algorithm that runs in θ(n 6 ) and Gilbert and Sonthalia [14] present an alternative algorithm that runs in O(n 5 ). Both of these algorithms are impractical and cannot be used on large data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we would need a general metric repair algorithm. Fan, et al [18] present an algorithm that runs in θ(n 6 ) and Gilbert and Sonthalia [14] present an alternative algorithm that runs in O(n 5 ). Both of these algorithms are impractical and cannot be used on large data sets.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of approach makes assumptions of certain Euclidean distance properties, e.g., symmetry and triangle inequality. However, such assumptions may not always hold, e.g., triangle inequality violations (TIVs) are commonly found in practice [9], [10]. To overcome these problems, matrix factorization are used [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to noise, missing data, and other corruptions, in practice, these distances do not often adhere to a metric. Motivated by these observations and early work by Brickell et al [5], Fan et al [8] and, independently, Gilbert and Jain [11] respectively formulated the Metric Violation Distance (MVD) and the sparse metric repair (SMR) problems. Formally, the problem both authors studied was given a distance matrix, modify as few entries as possible so that the repaired distances satisfy a metric.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tenenbaum et al [19] showed that Isomap can be approximated by looking at only a few key points. In many of these cases, using the approximation algorithms in [8,11] may not produce meaningful results. As a more algorithmic example, let us consider traveling salesman problem (TSP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation